Validation of a Brazilian version of the moral sensitivity questionnaire - Dalla Nora, Carlise R. (2019)
Background: Moral sensitivity has been identified as a foundational component of ethical action. Diminished or absent moral sensitivity can result in deficient care. In this context, assessing moral sensitivity is imperative for designing interventions to facilitate ethical practice and ensure that nurses make appropriate decisions. Objective: The main purpose of this study was to validate a scale for examining the moral sensitivity of Brazilian nurses. Research design: A pre-existing scale, the Moral Sensitivity Questionnaire, which was developed by Lützén, was used after the deletion of three items. The reliability and validity of the scale were examined using Cronbach’s alpha and factor analysis, respectively. Participants and research context: Overall, 316 nurses from Rio Grande do Sul, Brazil, participated in the study. Ethical considerations: This study was approved by the Ethics Committee of Research of the Nursing School of the University of São Paulo. Findings: The Moral Sensitivity Questionnaire contained 27 items that were distributed across four dimensions: interpersonal orientation, professional knowledge, moral conflict and moral meaning. The questionnaire accounted for 55.8% of the total variance, with Cronbach’s alpha of 0.82. The mean score for moral sensitivity was 4.45 (out of 7). Discussion and conclusion: The results of this study were compared with studies from other countries to examine the structure and implications of the moral sensitivity of nurses in Brazil. The Moral Sensitivity Questionnaire is an appropriate tool for examining the moral sensitivity of Brazilian nurses.